Metode Microteaching dalam Mengembangkan Keterampilan Dasar Mengajar dan Efikasi Diri Mahasiswa - Muhammad Saefullah; Arini Haqiqota Hayati; Shofa Taufiqika; Mamluatul Muarifah; Arini Aula Aimatun Nisa; Eqtada Binnabil Mustofa; Misbahul Baihaqi; Ali Mustofa; Balya Jayanda Daniel; Annisa Audila Rahmawati; Khoirul Mukti; Alya Mufti Tanfirotun Khusna (Reflection : Islamic Education Journal, 2026)
Microteaching is an innovative educator training method aimed at developing basic teaching skills and fostering student self-efficacy through a micro-scale approach. This study describes how teaching simulations with limited duration, audience size, and material focus can facilitate the transformation of pre-service teachers' pedagogical competence. Using a qualitative approach, the research found that microteaching functions as a "safe laboratory" for students to explore teaching creativity without the risk of systemic failure. The skill development process includes mastering stimulus variation techniques through the use of visual and audiovisual media, such as PowerPoint and instructional videos, as well as strengthening instructional communication styles. Furthermore, students' self-efficacy increases significantly through a cycle of constructive feedback from peers and supervisors, enabling reflection-on-action. The results conclude that the re-plan and re-teach mechanisms are crucial in shaping professional and permanent teaching behaviors before students enter actual classroom environments. These findings highlight the importance of microteaching in developing both the technical and reflective skills necessary for effective teaching practice.